Divided Loyalists or Conditional Cooperators? Creating Consensus About Cooperation in Multiple Simultaneous Social Dilemmas. (December 2014) - McCarter, Matthew W.; Samek, Anya; Sheremeta, Roman M.
The current social dilemma literature lacks theoretical consensus regarding how individuals behave when facing multiple simultaneous social dilemmas. The divided-loyalty hypothesis, from organizational theory, predicts that cooperation will decline as individuals experience multiple social dilemmas with different compared to the same group members. The conditional-cooperation hypothesis, from behavioral economics, predicts that cooperation will increase as individuals experience multiple social dilemmas with different compared to the same group members. We employ a laboratory experiment to create consensus between these literatures and find support for the conditional-cooperation hypothesis. The positive effect of interacting with different group members comes from participants having an opportunity to shift their cooperative behavior from the less cooperative to the more cooperative group.